Researching in the age of Covid-19: - Kara, Helen; Khoo, Su-Ming (Policy Press, an imprint of Bristol University Press, 2020)
"As researchers continue to adapt, conduct and design their research in the presence of COVID-19, new opportunities to connect research creativity and ethics have opened up. Researchers around the world have responded in diverse, thoughtful and creative ways -adapting data collection methods, fostering researcher and community resilience, and exploring creative research methods. This book, part of a series of three Rapid Responses, explores dimensions of creativity and ethics, highlighting their connectedness. It has three parts: the first covers creative approaches to researching. The second considers concerns around research ethics and ethics more generally, and the final part addresses different ways of approaching creativity and ethics through collaboration and co-creation. The other two books focus on Response and Reassessment, and Care and Resilience. Together they help academic, applied and practitioner-researchers worldwide adapt to the new challenges COVID-19 brings"--Publisher's description
Keywords: Social sciences -- Research.; COVID-19 (Disease) -- Research.; Creative ability.; COVID-19 -- psychology; Social Sciences -- methods; Ethics, Research; Research Design; Creativity; Sciences sociales -- Recherche.; COVID-19 -- Recherche.; Créativité.; creativity.; SOCIAL SCIENCE / Methodology.; Creative ability; COVID-19 (Disease) -- Research; Social sciences -- Research